Development of a Highly Efficient SOFC Module Using Two‐stage Stacks and a Fuel Regeneration Process1. Issue 4 (18th August 2017) - Nakamura, K.; Ide, T.; Taku, S.; Nakajima, T.; Shirai, M.; Dohkoh, T.; Kume, T.; Ikeda, Y.; Somekawa, T.; Kushi, T.; Ogasawara, K.; Fujita, K.
Abstract: A solid oxide fuel cell (SOFC) module using two‐stage stacks and a fuel regeneration process between them was developed in this study for the first time, to the best of the authors' knowledge. Upon configuring the first‐stage and second‐stage stacks and a steam reformer between them in the SOFC module, a gross output power of DC 2.27 kW was generated with gross power generation efficiency of DC 69.2% (lower heating value (LHV)), at a total fuel utilization rate of 86.3%. This technology enables operation at a very high total fuel utilization rate even while operating the stacks at a moderate fuel utilization rate (below 70%). Considering an auxiliary device loss (6%) and inverter loss (5%), the net power generation efficiency is estimated to be AC 61.8% (LHV); hence, the module is considered to exhibit a high power generation efficiency. Further increases in the power generation efficiency could be realized in the future by removing the CO2 from the anode off‐gas during the fuel regeneration process and/or operating the stacks at higher temperatures by decreasing heat leakage from the module.